An analysis of non-shariah compliant advertisement from website / Nur Syatinie Mat Hassan - Mat Hassan, Nur Syatinie (2019)
Contemporary advertisement practices have created many social and ethical problems due to their materialistic focus. The effect of these problems can also be seen in many Muslim countries including Malaysia in terms of diversion from their cultural and religious values. This paper attempts to integrate the Islamic business ethics in contemporary advertisement practices to find the solution of the ethical dilemma which is created by these materialistic advertisement practices. The focus of Islamic way of business is not just to earn profit but to serve the society. The human welfare is the gist of Islamic business ethics. This paper attempts to evaluate advertisement in terms of Quran and Hadiths of the Holy Prophet (PBUM) and discuss unethical aspects of the contemporary advertisement practices.